THE EFFECTIVENESS OF INTERCULTURAL COMMUNICATION ON WIDYAISWARA WITH STUDENTS IN SOUTH SUMATRA PROVINCE - Prihatini, Lishpsari (Awang Long Law Review, 2021)
Widyaiswara is a Civil Servant (PNS) who is appointed as a functional official by an authorized official with the duties, responsibilities, authority to educate, teach, and / or train Civil Servants (PNS) at government education and training institutions. Widyaiswara is a job related to education and training for ASN Dan employees. Widyaiswara must be able to have a skill, namely communication skills, especially communication between cultures. Similarities of Teachers, Lecturers Lecturers If all this time teachers have carried out educational tasks that teach and educate school children from elementary to high school levels, then it is different for their lecturers to also carry out the task of educating and teaching students who study at a university or campus. While widyaiswara has the main task of carrying out education, teaching and training (Dikjartih) for ASN employees so widyaiswara's main task is to educate, teach and train employees of the state civil apparatus in this country through both pre-service training, leadership training and other functional and technical training. the progress of the government bureaucracy in this country also depends on the role of widyasiwara throughout Indonesia. Widyaiswara is a teacher who carries out an activity called Teaching, Teaching and Training (Dikjartih). As an illustration, we devote this paper to the lecturers who we observe on a micro level who consist of various scientific disciplines and various cultures.